PERANAN PENGGUNAAN KARTU DEBIT BERLOGO GERBANG PEMBAYARAN NASIONAL (GPN) : Mahasiswa Universitas Pembangunan Nasional Veteran Jakarta - Dinna Nurbaeiti (2021)
The form of the banking revolution brought a lot of convenience. These various facilities have brought the economy to a higher stage so that efficiency is a major topic in the digital era and can help the government in realizing a cashless society. With the existence of a national payment gateway (GPN) which was launched by Bank Indonesia to increase the efficiency of the payment system, now people can be relieved because it provides convenience and practicality in using debit cards with the GPN logo. Based on the study conducted aimed at knowing the switch to using cards with the GPN logo, knowing student interest in using cards with the GPN logo, knowing the benefits of GPN in their use, knowing the role of GPN in card use, it can be concluded that GPN has an important role in customers because it has an effect on effectiveness. a comprehensive national payment system, which was previously very cementative, has become interconnection and interoperability in payment channels, thus providing sufficient convenience to meet customer needs it shows people's interest in switching to cards with the national payment gateway (GPN) logo. Thus, both students and other levels of society can take advantage of technological advances in the banking revolution for the advancement of the Indonesian economy.